2012
DOI: 10.1007/bf03262290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Respiratory Muscle Training on Exercise Performance in Healthy Individuals

Abstract: RMT improves endurance exercise performance in healthy individuals with greater improvements in less fit individuals and in sports of longer durations. The two most common types of RMT (inspiratory muscle strength and respiratory muscle endurance training) do not differ significantly in their effect, while combined inspiratory/expiratory strength training might be superior. Improvements are similar between different types of sports. Changes in performance can be detected by constant load tests, time trials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
239
3
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(262 citation statements)
references
References 104 publications
9
239
3
11
Order By: Relevance
“…To distinguish the effects of the CM/IM intervention from the known effects of IMT upon running performance (4,12), all participants completed a 4-week period of IMT prior to the interval training intervention phase of the study. Subsequently, both groups undertook 6-week interval running training, but only the ICT group received the CM/IM intervention.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…To distinguish the effects of the CM/IM intervention from the known effects of IMT upon running performance (4,12), all participants completed a 4-week period of IMT prior to the interval training intervention phase of the study. Subsequently, both groups undertook 6-week interval running training, but only the ICT group received the CM/IM intervention.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…A recent systematic review showed that in normal subjects, the combination of IMT plus EMT is more effective in increasing the performance exercise compared with IMT or the control group. 33 Fig. 2.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Threshold group had a higher MIP from the beginning, which led to higher loads used by the subjects in comparison to POWERbreath plus group Figure 6. For Threshold® device, the load ranges are limited to 41 cmH 2 O, and one of our subjects had exceeded 41 cmH 2 O when she reached her 70% and 80% of MIP (45.5-52 cmH 2 O respectively) so we have been forced to use a sustained load of 41 cmH 2 O for the remaining two weeks. On the other hand, POWERbreath plus® device had higher loads up to 78 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, muscle training devices play a very distinguished role in improving muscle activities [2].…”
Section: Introductionmentioning
confidence: 99%